Relationship between Leisure and Happiness at Work among TVET Instructors - Mohd.Romero, Mohamad Sadek; Zaiton, Hassan; Mark, Edmund Kasa; Surena, Sabil (2022)
Various scholars have investigated the origins and linkages of workplace happiness. However, little is known regarding the relationship between Leisure Satisfaction, Leisure Attitude, and Leisure Motivation in the context of Happiness at Workplace (HAW) among Malaysians’ TVET instructors. The purpose of the study is to investigate the relationship of leisure activities and happiness at work among TVET instructors in Sarawak. The study utilizes a survey approach employing a set of standardized questionnaires via Google Form. The sample comprises 122 respondents from a Public TVET institution in Sarawak, Malaysia. Data were analyzed using IBM SPSS Ver 26.0, employing Pearson correlation and multiple regression. Correlation studies revealed that all the components Leisure Satisfaction and Leisure Attitude are positively correlated with Happiness at Workplace. The higher Leisure Satisfaction and attitude will increase the Happiness at Workplace of TVET instructors. The findings revealed that leisure satisfaction have the significant contribution to happiness at work among instructors. The findings enable the organization to broaden their perspective and serve as a reminder that supporting and encouraging leisure activities of their instructors in the workplace can result in Happiness at Workplace.